2019
DOI: 10.26905/jmdk.v7i2.3247
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Motivasi, Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan

Abstract: The purpose of this research is to analyze the influence of motivation, communication and organizational culture to employee performance. The object of this study is Merdeka University Pasuruan. Data collected through questionnaires given to 42 respondents of educational staff taken by census method. The results show that: 1) motivatian has a significant effect on employee performance, 2) communication does not have a significant effect on employee performanc,e 3) organizational culture has a significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 1 publication
1
6
0
6
Order By: Relevance
“…This is because organizational culture serves as an adhesive system between employees, superiors and all members of the organization and is used as a reference to behave in an organization to achieve organizational goals [6]. This is in accordance with the results of research by [9], [4], which showed that the results of organizational culture had a positive effect on employee performance. Based on the above, the following hypothesis is proposed: H3: Organizational culture positively affects employee performance The Effect of Organizational Commitment on Employee Performance Organizational commitment is one of the basic attitudes that control the heart and mind in relation to the responsibility in completing the work well so that good performance is also obtained [24].…”
Section: The Effect Of Work Environment On Employee Performancesupporting
confidence: 76%
“…This is because organizational culture serves as an adhesive system between employees, superiors and all members of the organization and is used as a reference to behave in an organization to achieve organizational goals [6]. This is in accordance with the results of research by [9], [4], which showed that the results of organizational culture had a positive effect on employee performance. Based on the above, the following hypothesis is proposed: H3: Organizational culture positively affects employee performance The Effect of Organizational Commitment on Employee Performance Organizational commitment is one of the basic attitudes that control the heart and mind in relation to the responsibility in completing the work well so that good performance is also obtained [24].…”
Section: The Effect Of Work Environment On Employee Performancesupporting
confidence: 76%
“…Komunikasi dapat mempengaruhi kinerja karyawan. Hal ini sesuai dengan karya Shinta dan Siagian (2020) dan Kartini (2021).…”
Section: Pendahuluanunclassified
“…The relationship between motivation and employee performance has been studied by Erwatiningsih (2019), state that employee motivation has a connection with employee performance. Muhajir (2019) also conducted (2019) a similar study stating that motivation can influence employee performance.…”
Section: Introductionmentioning
confidence: 99%